2016
DOI: 10.7860/jcdr/2016/23278.8800
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of the Occipital Condyle and Its Surgical Importance

Abstract: IntrOductIOnThe human Occipital Condyle (OC) is the distinctive bony structure linking the skull and the vertebral column [1]. The OC partly cover the fringe of the foramen magnum anteriorly and form an articulation with the superior articular facets on the lateral masses of the atlas inferiorly. Each OC which is oval in outline and oriented obliquely is traversed by hypoglossal canal. A condylar fossa is situated just posterior to the OC and can contain a posterior condylar canal for an emissary vein from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 9 publications
4
23
4
1
Order By: Relevance
“…Nevertheless, the results were nearly agreed with that of Indian skulls demonstrated by Saluja [20] (28.16 mm and 26.93 mm respectively), but slightly higher than the measurements of Pereira [19] (26.07 mm and 25.75 mm respectively). Also Pereira showed that the mean distances between the basion to the midpoint of the right OC was 14.87 mm and for the left one was 14.63 mm that were higher than the Egyptian measurements shown by the present study (16 mm and 15.78 mm respectively).…”
Section: Occipital Condylessupporting
confidence: 77%
See 1 more Smart Citation
“…Nevertheless, the results were nearly agreed with that of Indian skulls demonstrated by Saluja [20] (28.16 mm and 26.93 mm respectively), but slightly higher than the measurements of Pereira [19] (26.07 mm and 25.75 mm respectively). Also Pereira showed that the mean distances between the basion to the midpoint of the right OC was 14.87 mm and for the left one was 14.63 mm that were higher than the Egyptian measurements shown by the present study (16 mm and 15.78 mm respectively).…”
Section: Occipital Condylessupporting
confidence: 77%
“…According to Indian skulls, Saluja [20] found that the mean right condylar sagittal angle was 41.10° and the left one was 44.04° which indicates higher condylar angles in Indians than in Egyptians. On the other hand, they also demonstrated in their study that the mean AICD was 17.81 mm which was nearly similar to our results.…”
Section: Occipital Condylesmentioning
confidence: 99%
“…[29] The mean anterior (AICD) and posterior intercondylar (PICD) distances for the Nigerian skulls were found to 18.09±2.15mm and 30.85±2.98mm. The mean AICD observed in this study was larger than the values;15.39±7.0mm, 17.63mm and 17.81±2.93mm reported by Agnihotriet al (2014), [20] Kumarand Nagar (2014), [30] and Salujaet al (2016), [16] respectively, but lower than the values of Naderiet al (2005), [31] and Mahajan et al (2011), [26] as they reported 21mm, 21.28±3.03mm, 21.28±3.03mm. However the mean PICD obtained in this study was much smaller than the values of Naderiet al (2005), [31] [41.6mm], Mahajan et al (2011), [26] [40.61±3.34mm], Agnihotriet al (2014), [20] [35.60±8.4mm], Kumarand Nagar (2014), [30] [42.02mm] and Salujaet al (2016), [16] [38.91±4.16mm].…”
Section: Resultscontrasting
confidence: 72%
“…[17] Kavithaet al (2013), [28] reported 21.97mm and 22.34mm for the right and left respectively while Salujaet al (2016), [16] reported mean values of 22.75±2.90mm for Indians. Due to the irregularity in the dimension of the width of OC, this study evaluated two dimensions; minimum (MnOC) and maximum (MxOC) width.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation